Farming as a Sustainable Vocation for Self-Reliance and Employability of Adults - Adindu, K. C. (Journal of Research in Adult and Continuing Education, 2024)
The paper discussed farming as a sustainable vocation for self-reliance and employability of adults, considering the current economic environment emphasizing the need for sustainable vocational choices to overcome the challenges of economic down turn where wages cannot sustain the inflation rate of the prices of goods and services. Basically, the purpose of the paper is to create more awareness on the need for adopting cultural practices in farming and to re-awaken the consciousness of seeing farming as an attractive, profit making business not as a mere hobby for adults. Literatures reviewed from textbooks and journals identified cultural practice as a way of sustaining soil fertility and increasing productivity. The rise of crime, hunger and theft in the society are attributable to poor attitude to farming profession as a result of get rich quick syndrome and poor attitude to farming also leads to low productivity of farm products and low productivity of farm products. The paper discussed the concept of farming; sustainable vocation and farming, self-reliance and farming; farming as the panacea for the employability of adultery and Vocational Adult Education Programme. The paper concludes that farming remains a sustainable vocation that the paper does not aim to turn every subsistence farmer into commercial farmer it should inspire farmers to think and make the right choices for profit it is recommended that the government should organize sensitization conferences, seminars and workshops to educate communities on the basic cultural practice in order to make farming more attractive through establishing functional farm settlement schemes and distributing improved farm inputs to farmers among others. The accomplishment of the recommendation will not only increase food production but will also attract youths for employability, sustainability and be self-reliant in farming profession.
Keywords: Farming; sustainable vocation; self-reliance; employability of adults; vocational adult education